PENGARUH STRUKTUR KEPEMILIKAN SAHAM, RETURN ON EQUITY DAN LEVERAGE TERHADAP DIVIDEND PAYOUT RATIO (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2018) - Dien Hawa, Ghassani Malda; Widyarti, Endang Tri (Diponegoro Journal of Management, 2020)
This research aims to examine the effect of ownership structure, return on equity and leverage on dividend payout ratio. The ownership structure is devided to foreign ownership and government ownership as independence variables, while dividend payout ratio as dependent variable. Return on equity and leverage as independence variables, while dividend payout ratio as dependent variable.This research used secondary data with population consists of 234 manufacturing companies listed in Indonesia Stock Exchange in the period of 2015-2018. The purposive sampling method used was used in selecting the research sample and 34 manufacturing companies that consistently distributed dividends during the research period. Multiple linear regression technique are chosen for this research statistic analysis. This research has fulfilled the classical assumption test requirements and used the t test to determine the significance of the influence of the variable ownership structure, return on equity and leverage on the dividend payout ratio.The result of this research shows that return on equity has a positive significant effect on the dividend payout ratio. Meanwhile, foreign ownership and government ownership, have no significant effect on the dividend payout ratio. Leverage has a negative significant effect on the dividend payout ratio.